2016
DOI: 10.1521/jscp.2016.35.7.525
|View full text |Cite
|
Sign up to set email alerts
|

An Unclear Self Leads to Poor Mental Health: Self-Concept Confusion Mediates the Association of Loneliness with Depression

Abstract: Past research has established that loneliness is associated with both self-concept confusion and depression. The present work ties these disparate lines of research together by demonstrating that self-concept confusion mediates the relationship

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…The results suggest that satisfactory relationships with others, especially with significant others, are a key to the validation of the true self, which consequently translates to well-being. This thesis is consistent both with the classic theoretical concepts indicating the social sources of self (Mead 1934;Wallace and Tice 2012), contemporary concepts of authenticity (Wang 2016;Schmader and Sedikides 2017) and the results of studies that demonstrate that feeling socially disconnected predicts a low level of self-concept clarity (Ayduk et al 2009;Slotter et al 2010;Richman et al 2016). Lowered authenticity as an effect of loneliness may be explained by the accompanying social rejection or exclusion, the mechanisms related to psychological defense.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The results suggest that satisfactory relationships with others, especially with significant others, are a key to the validation of the true self, which consequently translates to well-being. This thesis is consistent both with the classic theoretical concepts indicating the social sources of self (Mead 1934;Wallace and Tice 2012), contemporary concepts of authenticity (Wang 2016;Schmader and Sedikides 2017) and the results of studies that demonstrate that feeling socially disconnected predicts a low level of self-concept clarity (Ayduk et al 2009;Slotter et al 2010;Richman et al 2016). Lowered authenticity as an effect of loneliness may be explained by the accompanying social rejection or exclusion, the mechanisms related to psychological defense.…”
Section: Discussionsupporting
confidence: 84%
“…The causal direction of the relationship between loneliness and accessibility, as well as clarity of the true self, may be indicated by data originating from both longitudinal and experimental studies. In the recently published longitudinal research by Richman et al (2016), the negative relationship between loneliness and depression was shown to be mediated by self-concept confusion over time. Then again, experimental studies have revealed that an experience of being socially rejected increases self-uncertainty (Yavuz Güzel and Şahin 2018) and causes people to avoid self-awareness (Twenge et al 2003).…”
Section: Authenticity and Lonelinessmentioning
confidence: 98%
See 1 more Smart Citation
“…Self is fundamentally interpersonal ( Morf and Mischel, 2012 ). Interactions with others influence one’s sense of self-esteem, self-worth, which plays a quite important role in the definition of sense of self ( Richman et al, 2016 ). Having a good relationship with people around will fulfill one’s need of belonging and connection, which is implicitly constructed into individual’s self-concept.…”
Section: Introductionmentioning
confidence: 99%
“…As such, we cannot confirm the causal chain by which network disagreement impacts health and well-being as mediated by self-concept clarity. While longitudinal evidence suggests that self-concept clarity predicts later well-being (Richman et al, 2016;Shin, Steger, & Henry, 2016), other evidence suggests that the relationship is reciprocal (van Dijk et al, 2014). Thus, longitudinal or experimental evidence is needed to bolster the mediational pathways explored in Study 3. which there is a lot of consensus among your social network, where people tend to hold very similar opinions?…”
Section: Limitationsmentioning
confidence: 96%